(untitled) (Northern International Medical College Journal, 2022)
Background : Oligohydramnios is one of the pregnancy associated common complications facing by obstetrician which is associated with adverse maternal and perinatal outcome such as birth defects, miscarriage, intrauterine growth restriction, still birth, preterm birth, increased operative interference etc. Objective: To assess the impact of oligohydramnios on maternal and perinatal outcome. Methods: This cross-sectional descriptive study was conducted at Department of Obstetrics and Gynecology, BSMMU, Dhaka from October 2017 to March 2018.Total 50 patients were enrolled by purposive sampling method according to the inclusion and exclusion criteria. Clinical evidence of oligohydramnios was looked for & confirmed by ultrasonography (USG). Based on Amniotic fluid index (AFI)measurements patients were divided into two groups. Those who have AFI <5cm and 5-8cm. The significance of difference or comparison of means was measured by Chi square test. Maternal and perinatal outcome in pregnancies with oligohydramnios were compared with those with 5-8cm amniotic fluid volume. Results: The mean age of the study population was 23.3±4.06 years and majority of the cases were multipara (56%) and presented at term (58%). Borderline oligohydramnios (AFI 5-8cm) was found in 74% cases and severe oligohydramnios (AFI <5cm) were found in 26% cases. Most common etiological factor was idiopathic. Fifteen cases (30%) had vaginal delivery and caesarean section rate 70%, no maternal mortality occurred in this study, perinatal mortality rate was 10%, low birth weight baby was 63.6% and NICU admission rate was 53.8%. Conclusion: An antepartum or intrapartum oligohydramnios is associated with significantly increased incidence of caesarean section for fetal distress and increased incidence of low-birth-weight babies and increased rate of neonatal complications. Northern International Medical College Journal Vol. 12 No.1 July 2020, Page 489-492